2015
DOI: 10.1111/hpb.12440
|View full text |Cite
|
Sign up to set email alerts
|

Hospital costs of complications after a pancreatoduodenectomy

Abstract: This study provides an in-depth analysis of hospital costs and identifies factors that are associated with substantial cost consequences of specific complications occurring after a PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 43 publications
0
23
1
Order By: Relevance
“…POPF increased costs more than threefold and hospitalisation length more than twofold over uncomplicated patients, agreeing with several cost studies of POPF. 7,16 Post pancreatectomy haemorrhage (PPH) was the costliest individual complication in our cohort, with an incidence of 9%. Our results correspond with Santema et al's 16 study, which found that PPH was costlier than POPF and DGE, with an incidence of 12%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…POPF increased costs more than threefold and hospitalisation length more than twofold over uncomplicated patients, agreeing with several cost studies of POPF. 7,16 Post pancreatectomy haemorrhage (PPH) was the costliest individual complication in our cohort, with an incidence of 9%. Our results correspond with Santema et al's 16 study, which found that PPH was costlier than POPF and DGE, with an incidence of 12%.…”
Section: Discussionmentioning
confidence: 99%
“…7,16 Post pancreatectomy haemorrhage (PPH) was the costliest individual complication in our cohort, with an incidence of 9%. Our results correspond with Santema et al's 16 study, which found that PPH was costlier than POPF and DGE, with an incidence of 12%. Considering the relative dearth of studies analysing the cost of PPH following PD compared to other complications such as POPF and DGE, future studies may aim to further clarify this important complication.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical site infections following PD vary from 7 to 32% , and contribute to increased length of hospital stay and re‐admissions . The presence of a postoperative SSI increases hospital costs by 32.4% after PD . The extra cost incurred is estimated at $15,336 per complication, with wound infection considered as the most common infectious complication .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a postoperative SSI increases hospital costs by 32.4% after PD . The extra cost incurred is estimated at $15,336 per complication, with wound infection considered as the most common infectious complication . More importantly, postoperative wound infection delays adjuvant chemotherapy in patients with pancreatic cancer and doubles the risk of chemotherapy omission .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation